Development of Financial Innovations and Technologies (Ustozlar uchun, 2024)
This article highlights the history of credit cards and their significance in the field of financial innovations. It analyzes the contribution of credit cards to societal development in connection with Adam Smith's "invisible hand" theory. The process from the initial introduction of credit cards to the competition between banks and the formation of the modern financial system is thoroughly examined. Additionally, the state's intervention in economic processes through the "visible hand" and measures against monopolies are discussed. The article demonstrates that credit cards are not only a convenience tool but also a symbol of revolutionary changes in the global economy